Barriers and Facilitators to Adherence to Exercise-Based Cardiac Rehabilitation Among Coronary Artery Disease Patients: A Scoping Review - Zhao X; Zhang S; Zhang F; Wu X; Zhang Z; Liu Y; Jiang J; Li Z; Li S; Zheng S; Yang X; Ju X; et al. (Journal of Multidisciplinary Healthcare)
Xinqi Zhao,1,* Shi Zhang,2,* Fan Zhang,2 Xinyu Wu,1 Zhe Zhang,1 Yue Liu,2 Junwen Jiang,2 Zheng Li,2 Siqi Li,2 Sicheng Zheng,2 Xiao Yang,3 Xing Ju,1 Hang Li,4 Lihong Gong,2 DeZhao Kong2,5,6 1Liaoning University of Traditional Chinese Medicine, Shenyang, Liaoning, People’s Republic of China; 2Affiliated Hospital of Liaoning University of Traditional Chinese Medicine, Shenyang, Liaoning, People’s Republic of China; 3The Second Affiliated Hospital of Liaoning University of Traditional Chinese Medicine, Shenyang, Liaoning, People’s Republic of China; 4Shenyang Medical College, Shenyang, Liaoning, People’s Republic of China; 5Peking University Frist Hospital, Beijing, People’s Republic of China; 6Peking University Health Science Center, Beijing, People’s Republic of China*These authors contributed equally to this workCorrespondence: DeZhao Kong, Affiliated Hospital of Liaoning University of Traditional Chinese Medicine, Shenyang, Liaoning Province, China; Peking University Frist Hospital, Beijing, China; Peking University Health Science Center, No. 28, Xibahenanli, Chaoyang District, Beijing, People’s Republic of China, Email dezhaok2007@163.com Lihong Gong, Affiliated Hospital of Liaoning University of Traditional Chinese Medicine, No. 79, Chongshan East Road Huanggu District, Shenyang, Liaoning, People’s Republic of China, Email 215922524@qq.comBackground: Exercise-based Cardiac Rehabilitation (EBCR) is widely recognized as a crucial intervention for improving the health outcomes of patients with coronary artery disease (CAD). However, its implementation remains insufficient in many regions, and patient adherence to EBCR is generally low. This limitation hinders the full potential of rehabilitation, necessitating a deeper exploration of the factors influencing exercise adherence and the development of targeted intervention strategies.Objective: This study aims to identify the barriers and facilitators affecting ERCR adherence among CAD patients and provide intervention recommendations for clinical practice.Methods: A systematic search was conducted across nine databases, including PubMed, Cochrane Library, Embase, Web of Science, EBSCO, CNKI, Wanfang, VIP, and CBM. Using the Theoretical Domains Framework and the COM-B model, a thematic analysis was performed to categorize influencing factors identified in the included studies. These factors were mapped onto the Behaviour Change Wheel, and the APEASE criteria were applied to determine appropriate intervention functions. Finally, Behaviour Change Techniques were matched to these intervention functions.Results: Seventeen studies were included, identifying multiple core domains of the Theoretical Domains Framework influencing EBCR adherence. The most significant domains were social influences, beliefs about consequences, and environmental context and resources. The primary barrier was patients’ negative attitudes toward EBCR, whereas the most prominent facilitator was a strong social support network.Conclusion: This study systematically analyzed the determinants of EBCR adherence based on the Theoretical Domains Framework and COM-B model, constructing theoretically supported intervention strategies and providing new insights for optimizing EBCR implementation. Through precise Behaviour Change Techniques mapping, the proposed personalized interventions can enhance patients’ motivation for rehabilitation, improve EBCR adherence, and offer empirical support for future EBCR intervention design and implementation.Keywords: exercise-based cardiac rehabilitation, theoretical domain framework, behavior change wheel, behavior change technique, barriers, facilitators, adherence